2013
DOI: 10.1002/adma.201300636
|View full text |Cite
|
Sign up to set email alerts
|

Electric‐Field‐Dependent Spin Polarization in GdN Spin Filter Tunnel Junctions

Abstract: Tunnel junctions incorporating GdN ferromagnetic semiconductor barriers show a spin polarization exceeding 90% and a high conductance. These devices show an unusual low-bias conductance peak arising from a strong bias-dependence of the spin polarization. This originates from a strong magneto-electric coupling within a double Schottky barrier formed with the NbN electrodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 32 publications
6
60
0
Order By: Relevance
“…The spin polarization at 15 K (P 15 K ) shown in Fig. 4e shows a similar trend with thickness as observed previously 9 .…”
Section: K)supporting
confidence: 86%
See 1 more Smart Citation
“…The spin polarization at 15 K (P 15 K ) shown in Fig. 4e shows a similar trend with thickness as observed previously 9 .…”
Section: K)supporting
confidence: 86%
“…These distortions from the behaviour expected for a perfect Fraunhofer pattern are due to the fact that thin film GdN has a low coercivity of 20-50 Oe (ref. 9) and because of their large area, our devices have multiple magnetic domains, and micromagnetic structure plays an important role in multidomain devices in distorting the I c (H) patterns 10 , especially in the switching regions. Because GdN has a high remnant moment, the second lobe in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Ludbrook and co-workers [20] were able to achieve a tunneling magnetoresistance ratio (TMR) of 35%. Later, Pal et al and Senapati et al [21,22] reported observing a spin polarization of conductance reaching 90% in a GdN film sandwiched between NbN electrodes.…”
Section: Introductionmentioning
confidence: 95%
“…It was also shown that this feature of the crystal depends on the lattice constant. In recent works [20][21][22] transport properties of GdN films were investigated experimentally. Ludbrook and co-workers [20] were able to achieve a tunneling magnetoresistance ratio (TMR) of 35%.…”
Section: Introductionmentioning
confidence: 99%
“…Good candidates for the tunneling barriers are europium chalcogenides (EuO and EuS) for which values of P ranging from 80 up to almost 100% have been reported. [13][14][15][16][18][19][20][21] Also very high spin-filtering has been reported in GdN barriers [22][23][24] with polarizations as large as 97% at 15 K (even larger values are expected as T decreases).…”
mentioning
confidence: 96%